1990
DOI: 10.1128/iai.58.12.4020-4029.1990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of hemolytic and phospholipase C activities of Pseudomonas cepacia

Abstract: By using a gene-specific fragment from the hemolytic phospholipase C (PLC) gene of Pseudomonas aeruginosa as a probe and data from Southern hybridizations under reduced stringency conditions, we cloned a 4.2-kb restriction fragment from a beta-hemolytic Pseudomonas cepacia strain which expressed hemolytic and PLC activities in Escherichia coli under the control of the lac promoter. It was found, by using a T7 phage promoter-directed expression system, that this DNA fragment carries at least two genes. One gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 33 publications
2
24
2
Order By: Relevance
“…In our study, only B. vietnamiensis isolates were shown to be hemolytic. The low percentage of clinical BCC isolates exhibiting the hemolytic activity described in this report correlates well with earlier findings of Nakazava et al (15) and Vasil et al (30). In contrast, our data differ from those of Bevivino et al (3), which found that almost all isolates (environmental and clinical) belonging to B. ambifaria were hemolytic and that the percentage of hemolytic environmental B. cenocepacia isolates was markedly higher than the percentage of clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, only B. vietnamiensis isolates were shown to be hemolytic. The low percentage of clinical BCC isolates exhibiting the hemolytic activity described in this report correlates well with earlier findings of Nakazava et al (15) and Vasil et al (30). In contrast, our data differ from those of Bevivino et al (3), which found that almost all isolates (environmental and clinical) belonging to B. ambifaria were hemolytic and that the percentage of hemolytic environmental B. cenocepacia isolates was markedly higher than the percentage of clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
“…However, all haemolytic strains produce detectable lecithinase activity, and strains of B. cepacia, whether haemolytic or non-haemolytic, appear to produce detectable amounts of extracellular PLC activity. In contrast to the consistent patterns observed in the PLC gene of P. aeruginosa there is hypervariability in genetic organization of the PLC gene of B. cepacia [37]. The variable manner in which a B. cepacia PLC specific gene probe hybridizes with restricted B. cepacia DNA, the variability in expression of haemolytic and PLC activities of different strains, and the association of DNA arrangements with conversion of an Hly + to an Hly-variant may be related to the relatively large number of distinct insertion sequences (IS) reported for B. cepacia (> 25) [37,38]: in contrast these elements have yet to be discovered in P. aeruginosa.…”
Section: Extraceilular Virulence Factorscontrasting
confidence: 88%
“…were haemolytic when erythrocytes from various animals were tested [37]. Unlike the PLC activity of P. aeruginosa the PLC activity in B. cepacia does not correlate with haemolytic activity [29,37].…”
Section: Extraceilular Virulence Factorsmentioning
confidence: 90%
See 2 more Smart Citations